Design and simulation of a multichannel sensing system for liquid refractometry based on integrated photonics - A.G. Zakoyan; G.S. Voronkov; V.S. Lyubopytov; A.K. Sultanov; E.P. Grakhova; R.V. Kutluyarov (Компьютерная оптика)
The paper proposes a new architecture for the photonic laboratory-on-a-chip sensing systems, where multiple sensors based on microring resonators (MRR) are fed by a MRR with low quality factor, working as a spectrum shaper. This architecture enables simultaneous intensity scanning of at least four MRR-based sensors on the silicon-on-insulator platform. We evaluated numerically the system’s sensitivity for various schemes of connecting the sensors and the spectrum shaper. The sensor’s sensitivity was 110 nm/RIU. The sensing system configuration largely determines its sensitivity, which reaches 1980 dB/RIU. The considered architecture may be useful for implementing fully integrated optical lab-on-a-chip structures, as well as distributed multichannel sensing systems.